An Update on Plant Photobiology and Implications for Cannabis Production - Eichhorn Bilodeau, Samuel; Wu, Bo-Sen; Rufyikiri, Anne-Sophie; MacPherson, Sarah; Lefsrud, Mark (Frontiers in Plant Science, 2019)
This review presents recent developments in plant photobiology and lighting systems for horticultural crops, as well as potential applications for cannabis (Cannabis sativa and C. indica) plant production. The legal and commercial production of the cannabis plant is a relatively new, rapidly growing, and highly profitable industry in Europe and North America. However, more knowledge transfer from plant studies and horticultural communities to commercial cannabis plant growers is needed. Plant photosynthesis and photomorphogenesis are influenced by light wavelength, intensity, and photoperiod via plant photoreceptors that sense light and control plant growth. Further, light properties play a critical role in plant vegetative growth and reproductive (flowering) developmental stages, as well as in biomass, secondary metabolite synthesis, and accumulation. Advantages and disadvantages of widespread greenhouse lighting systems that use high pressure sodium lamps or light emitting diode (LED) lighting are known. Some artificial plant lighting practices will require improvements for cannabis production. By manipulating LED light spectra and stimulating specific plant photoreceptors, it may be possible to minimize operation costs while maximizing cannabis biomass and cannabinoid yield, including tetrahydrocannabinol (or Δ9-tetrahydrocannabinol) and cannabidiol for medicinal and recreational purposes. The basics of plant photobiology (photosynthesis and photomorphogenesis) and electrical lighting systems are discussed, with an emphasis on how the light spectrum and lighting strategies could influence cannabis production and secondary compound accumulation.